2017
DOI: 10.1073/pnas.1620432114
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalisbacteriocin EntV inhibits hyphal morphogenesis, biofilm formation, and virulence ofCandida albicans

Abstract: Enterococcus faecalis, a Gram-positive bacterium, and Candida albicans, a fungus, occupy overlapping niches as ubiquitous constituents of the gastrointestinal and oral microbiome. Both species also are among the most important and problematic, opportunistic nosocomial pathogens. Surprisingly, these two species antagonize each other's virulence in both nematode infection and in vitro biofilm models. We report here the identification of the E. faecalis bacteriocin, EntV, produced from the entV (ef1097) locus, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
193
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(205 citation statements)
references
References 62 publications
9
193
2
1
Order By: Relevance
“…37 Furthermore, Graham et al (2017) demonstrated that a bacteriocin of Enterococcus faecalis potently inhibits hyphal growth. 38 In conclusion, our analysis confirmed that the ability to form biofilms especially with intermediate/high metabolic activity is related to higher mortality in candidaemia. Furthermore, it highlights that considering biofilm mass and metabolic activity equivalent may lead…”
Section: Et Al (2012) Proved That Intravenously Administered Planktonicsupporting
confidence: 74%
See 1 more Smart Citation
“…37 Furthermore, Graham et al (2017) demonstrated that a bacteriocin of Enterococcus faecalis potently inhibits hyphal growth. 38 In conclusion, our analysis confirmed that the ability to form biofilms especially with intermediate/high metabolic activity is related to higher mortality in candidaemia. Furthermore, it highlights that considering biofilm mass and metabolic activity equivalent may lead…”
Section: Et Al (2012) Proved That Intravenously Administered Planktonicsupporting
confidence: 74%
“…Morales et al (2013) showed that phenazines derived from P aeruginosa impair C albicans metabolic activity and influence the cellular morphology, cell‐cell interactions and biofilm formation . Furthermore, Graham et al (2017) demonstrated that a bacteriocin of Enterococcus faecalis potently inhibits hyphal growth …”
Section: Discussionmentioning
confidence: 99%
“…4d). Similarly, Enterococcus faecalis secretes the bacteriocin EntV, which inhibits C. albicans hyphal and biofilm formation and disrupts mature C. albicans bio-films 142 . Finally, the LuxS quorum sensing system in S. gordonii is needed for the increase in biomass observed when S. gordonii and C. albicans form a dual-species bio-film 125 .…”
Section: Polymicrobial Biofilmsmentioning
confidence: 99%
“…Microbial biofilms account for more than 80% of microbial infections in the body. E. faecalis also colonizes the root canal and the apex surface in the form of a biofilm . Therefore, the E. faecalis biofilm is the object that root canal disinfectant needs to remove .…”
Section: Resultsmentioning
confidence: 99%